Pedagogical Conditions for the Effective Formation of Creative Thinking of Art Students - Assem, Abizhanova; Almaz, Nurazkhan; Daulet, Kabylov; Aliya, Mombek; Raushan, Kanapiyanova; Gulmira, Tugelbayeva; Ulbossyn, Aimbetova (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
The essence of the concept "creative thinking" is considered, and its working definition is formulated. Special attention is given to the identification of pedagogical foundations of future teachers' creative thinking development, which accounting will promote the increase of the efficiency of the considered process. Future teachers' creative thinking development is advantageously realized in the course of students’ vocational training, during which it is necessary to rely not only on mental development regularities knowledge (theoretical thinking, creative thinking peculiarities, sustained attention, imagination, and integration of memory) and students' individual characteristics (maturity of motivation to creative activities, the maturity of speech, volitional powers) but also on the competently organized didactic process (training to work with the concepts and their use, application of the system of creative tasks, developing the ability to overcome intellectual difficulties). Results of students’ activity studying on the basis of creative tasks have shown that creative thinking skills development depends on the students' thinking orientation in the processing of the received educational information; Also, creative thinking skills development depends on students' subjective attitude towards tasks, that is going to be helpful them during the educational process. This study aims to examine the essence of the concept of "creative thinking" and identify pedagogical foundations for its development in future teachers. The following methods of scientific and pedagogical research are used to achieve the objectives: the methods of theoretical research: the analysis of psychological and educational literature; methods of empirical research: students' activity products' studying, observation, conversation, pedagogical experiment.